2021
DOI: 10.1007/s11818-021-00301-z
|View full text |Cite
|
Sign up to set email alerts
|

Modularized iCBT‑I self-learn training for university staff—prevention and early intervention in the SARS-CoV-2 crisis

Abstract: Background Insomnia is a widespread disease in adults and has a high prevalence rate. As sleep disturbances are a risk factor concerning mental and physical health, prevention and early intervention are necessary. Thus, the aim of this study was to implement a self-learning prevention and early intervention training for university staff members. We adapted an established cognitive behavioral therapy for insomnia (CBT-I) intervention as an online version for use during the severe acute respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…However, none of the aforementioned studies provide an effect size for the outcomes of mental health interventions. In addition, although some studies suggested good effectiveness of ICBT on sleep problems during the COVID-19 pandemic, they did not report an effect size of the improvement in mental health ( Schlarb et al, 2021 ; Zhang et al, 2020 ). Thus, we could not directly compare the effectiveness of these interventions; future RCTs should be conducted to compare the effects of different psychological interventions implemented during the pandemic.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, none of the aforementioned studies provide an effect size for the outcomes of mental health interventions. In addition, although some studies suggested good effectiveness of ICBT on sleep problems during the COVID-19 pandemic, they did not report an effect size of the improvement in mental health ( Schlarb et al, 2021 ; Zhang et al, 2020 ). Thus, we could not directly compare the effectiveness of these interventions; future RCTs should be conducted to compare the effects of different psychological interventions implemented during the pandemic.…”
Section: Discussionmentioning
confidence: 94%
“…To date, several studies have explored the efficacy of Internet-based mental health interventions on people affected by the COVID-19 pandemic ( Al-Alawi et al, 2021 ; Schlarb et al, 2021 ; Wei et al, 2020 ; Zhang et al, 2020 ; Zhou et al, 2020 ), while some smaller studies have focused on older adults ( Shapira et al, 2021 ; Goodman-Casanova et al, 2020 ), especially those living in nursing homes, during the COVID-19 pandemic. In line with emerging research, we conducted a feasibility study to examine ICBT's effectiveness in the treatment of psychological distress in older adults without cognitive impairment living in nursing homes in China during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve studies of psychological interventions on people during the SARS-CoV-2 pandemic were identified for inclusion [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. All studies were published in 2020 and 2021 and published in indexed journals.…”
Section: Resultsmentioning
confidence: 99%
“…Another study included health care workers without personal identifying information being collected [ 18 ]. The last four studies included the general population/adults with a mean age ranging from 42.0 to 45.0 years [ 20 , 29 ] and students with a mean age ranging from 8.2 to 31.0 years [ 21 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation